Clinical and pathological characteristics of cervical clear cell carcinoma in patients not exposed to diethylstilbestrol: a comprehensive analysis of 49 cases - Zeng, Jing; Jiang, Wei; Li, Kemin; Zhang, Mengpei; Chen, Jinghong; Duan, Yuanqiong; Li, Qingli; Yin, Rutie (Frontiers in Oncology, 2024)
Purpose: This study aimed to investigate the clinical and pathological characteristics, treatment strategies, and prognosis of cervical clear cell carcinoma (CCCC) in patients not exposed to diethylstilbestrol in utero.The patients diagnosed with CCCC at West China Second University Hospital of Sichuan University between January 2011 and Jun 2023 were enrolled for this retrospective study. The clinical characteristics and information on treatment and follow-up were collected. The Kaplan-Meier method and Cox regression analysis were performed to identify the relative variables for predicting progression-free survival (PFS) and overall survival (OS).Results: Of the 49 patients included, the Federation International of Gynecology and Obstetrics (FIGO) (2018) stage distribution was 37 (75.5%) stage I, 6 (12.2%) stage II, and 6 (12.2%) stage III. The median follow-up interval was 24.1 months. Six (12.2%) patients had a recurrence, and five (10.2%) patients died. The 5-year PFS rate was 86.8%, and the 5-year OS rate was 88.2%. No recurrence or death was detected in two patients who successfully completed fertility-preserving treatment and seven patients who underwent surgery to preserve ovaries. Two patients became pregnant, giving birth to two babies. The univariate analysis showed that FIGO stage, Pelvic lymph node (PLN) metastasis, lymph vascular space invasion, and depth of stromal invasion (P ＜ 0.05) were significantly associated with PFS and OS. However, no significant prognostic factors were identified in the multivariate analysis.Conclusions: Ovary-preserving treatment and fertility-preserving surgery are safe and feasible in early-stage CCCC. Surveillance other than adjuvant treatment may be a better choice for early-stage CCCC without any pathological risk factors. More targeted therapies and immunotherapy should be pursued in future studies.